Anak-Anak dalam Meja Perjamuan Allah: Meninjau Ulang Dasar-Dasar Kovenantal dan Eskatologis dalam Praktik Paedocommunion - Kurniawan, Jemima Carissa (Veritas : Jurnal Teologi dan Pelayanan, 2023)
The inclusion of children in the church’s liturgy of the Lord’s Supper (paedocommunion) is still a matter of debate today. One of the main reasons for excluding them is that they are not considered capable of expressing their faith independently. However, from a biblical perspective, we see that the Lord’s Supper cannot be separated from covenant theology, which states that children are part of God's covenant, with or without a declaration of faith. If so, forbidding a child to participate in the Lord’s Supper would ultimately amount to considering children as mere potential Christians and not de facto members of God's covenant. Given the importance of the Lord’s Supper for believers, this paper aims to revisit what the Bible says about paedocommunion as a form of sacrament that can be applied by churches in general. The author argues that as part of the covenant and kingdom of God, children should be allowed to participate in the Lord’s Supper to remember Christ's redemption for them and prepare for Christ's second coming. To this end, the author begins by outlining the essential foundation of the practice of Holy Communion according to 1 Corinthians 11:23-29. Then, the author provides the Old Testament equivalent to establish the covenantal viewpoint and the New Testament equivalent to establish the eschatological viewpoint. Finally, the author gives a brief explanation of how children can participate in the table of God.